Renter Power For Better Living: Cover with Acknowledgements and References - Mary N. Harrison (EDIS)
This document is FCS5230-01, one of a series of the Family Youth and Community Sciences Department, UF/IFAS Extension. Original publication date June 2002. Revised December 2005.